089 Assessing the impact of recommendations on drug prescriptions in intensive care units. (23rd September 2015) - Kuteifan, K; Berg, C; Mootien, J; Gutbub, A M; Navellou, J C; Quenot, JP
Abstract : Background and Objectives: The prescription is the starting line in the organisation of the drug circuit and determines the work of all those involved in the drug delivery process. The aim of our study was to assess drug prescription in the intensive care units (ICUs) of the College of intensivists of North-East France. Programme: A two-round clinical audit was conducted in four ICUs. All prescriptions written out over a 24-h period were reviewed by a doctor and a pharmacist in each ICU. Criteria for good prescribing practices were established and distributed to all team members. A reminder was issued 3 months later. The second round of the clinical audit was carried out 6 months after the first. Results: The number of prescriptions was 180 in the first round and 193 in the second. The non-conformity rate was 33.9% and 12.4%, respectively. The main errors in the two rounds were: adding an unsigned and unstamped (no date or time) prescription (70% vs 58%), unsigned change in dose (16% vs 9%), unsigned order to discontinue drug administration (18% vs 9%), administration of a drug that was not prescribed, no mention of dose, oral prescription, and noncompliance with dosage form. Discussion and Conclusion: The dispensation and administration of a drug depends on the prescription. The main risks when prescribing drugs are the prescription of a treatment unsuited to the patient's clinical condition, possible drug interactions and a lack of detail that may induce errors. Establishing and distributing guidelines is an essential step in reducing prescribing errors and managing drug-related risks in ICUs. In conclusion, the production and distribution of criteria helped lower the rate of non-conformity with prescriptions in ICUs. We are currently preparing Intranet distribution within our hospital of criteria for the most commonly used drugs administered by infusion or injection and a list of drugs that can be administered by gastric tube. Introduction: La prescription est le point de départ d'un des processus organisationnels majeurs qu'est le circuit du médicament. Elle conduit à structurer l'organisation du travail de tous les acteurs de la dispensation à l'administration. L'objectif de notre étude est d'évaluer la prescription médicamenteuse dans les services appartenant au Collège des réanimateurs du Nord-Est. Méthode: Un audit clinique, est réalisé dans 4 services de réanimation. Toutes les prescriptions d'une période de 24 heures ont été revues par un médecin et un pharmacien dans chaque service. Un référentiel de prescription a été réalisé et distribué à tous les membres des équipes médicales, avec une « piqûre de rappel » à 3 mois. Un deuxième relevé a été réalisé à 6 mois. Résultats: 180 prescriptions ont été relevées au premier tour, et 193 au deuxième. Les taux de non conformité étaient de 33, 9 % et de 12, 4 % respectivement. Les erreurs principales qui ont été notées sont : ajout de prescription non signée non horodatée (70 vs 58%), modification de posologie non signée(16 vs 9%), arrêt d'un traitement non signé (18 vs 9%), administration d'un médicament non prescrit, absence de posologie, prescription verbale et forme galénique non respectée. Discussion: La qualité d'une prescription du médicament conditionne celle des autres étapes : dispensation et administration. Les principaux risques encourus à cette étape de prescription d'une ligne thérapeutique sont liés à une inadéquation par rapport à l'état de santé du patient, une interaction délétère avec d'autres lignes thérapeutiques et/ou une insuffisance de précision génératrice d'erreurs. La diffusion des recommandations est un élément essentiel dans la maîtrise des erreurs de prescription et la gestion de risque lié aux médicaments en réanimation. Résultats: La réalisation et la diffusion de référentiel de prescription médicamenteuse a permis de baisser le taux de non conformité des prescriptions en réanimation. Des listes de diffusion « intranet » des médicaments les plus couramment utilisés avec modalités de perfusion ou d'injection ainsi que la liste des médicaments compatible avec un administration par une sonde gastrique sont en train d'être finalisées pour être diffusées dans notre hôpital.